THE CORRELATION OF VOCABULARY MASTERY AND READING COMPREHENSION AT STUDENTS OF SMK NEGERI 2 LUWUK - ST Marhana Rullu; Farel A. Bikas (English Education Study Program, 2021)
The aim of research is to know the correlation between vocabulary mastery and reading comprehension of eleventh grade students of SMK Negeri 2 Luwuk. This research used correlation design. The population were the students in class XI and consist of 32 students. In collecting data, the researcher used test and statistic SPSS 26 for measuring the score of vocabulary mastery and reading comprehension of students. After analyzing test score, the researcher found that the result rxy was 0.902, the result of significance level 5%. Therefore the result is higher than r table 0.902 > 0.5%. The level of correlation coefficient between variable X and Y is a perfect correlation. It is assumed that there is a correlation between vocabulary mastery and reading comprehension of students of SMK Negeri 2 Luwuk.